Fesibility Study on Increasing Water Use Efficiecy in (Thymus vulgaris L.) in Different Planting Pattern and Partial with Using Biochar - Kiomars Fakhri; Saeed Sayfzadeh; Mansour Sarajooghi; Seyed Alireza Valad Abadi; Ismail Hadidi Masouleh (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
The purpose of this field was to study the effect of biochar application and different planting patterns in different irrigation regimes on the growth and yield of thyme essential oil. The studied treatments include irrigation (irrigation of all furrows, irrigation of furrows as one in constant and one in variable (biochar (non-application of biochar and application of biochar at 8 tons per hectare) and planting pattern (single row cultivation) Thyme and cultivation of two rows of thyme) on the growth and yield of the thyme plant. This experiment was carried out in two cropping years of 1397 and 1398 in the form of split plots based on a randomized complete block design with three replications. The results showed that the highest yield of flowering branches was obtained in the treatment of irrigation of all furrows + application of biochar with mean of 1701 kg. ha-1. In this study, the highest yield of essential oil with 24.7 kg. ha-1 was obtained in the treatment of furrow irrigation as a constant interval + application of biochar + cultivation of two rows of thyme. Based on the results of this study, the application of biochar and two-row cultivation caused a significant increase in the yield of thyme essential oil. In general, despite the decrease in growth and yield of thyme dry matter, furrow irrigation treatments as one-to-one variables increased essential oil yield by significantly increasing the percentage of essential oil and reducing water consumption. Biochar treatment also had a positive effect on all vegetative and functional traits of thyme.